Smart Microalgae-Based Air Purification: A Self-Sustaining Alternative to Household Plants - Ferdynand, Hosea; Hoendarto, Genrawan; Chang, Calvin (MDP Student Conference, 2025)
A self-sustaining, Internet of Things-integrated microalgae photobioreactor (PBR) is proposed in this study as an alternative to traditional household air purifying plants. In order to optimize microalgae development while reducing human involvement, the system combines a tubular PBR with an automatic water exchange mechanism and real-time IoT monitoring. CO₂-enriched air is continuously injected by an air bubbler, boosting photosynthesis and oxygen production. A drainage system eliminates extra water to preserve nutritional balance, and a water replenishment tank with a solenoid valve ensures controlled water exchange. Essential variables such as pH, turbidity, dissolved oxygen, and CO₂ concentration are monitored by the IoT system, which also provides alerts when maintenance is required. Purified air may naturally diffuse thanks to the passive air gap, which ensures continuous air filtration. By utilizing biotechnology and intelligent automation, this low-maintenance, sustainable system provides an efficient automated alternative for conventional plants in indoor air purification.